2019
DOI: 10.5433/1679-0359.2019v40n3p1225
|View full text |Cite
|
Sign up to set email alerts
|

Addition of different probiotics to commercial feeds for piglets during the nursery phase

Abstract: In this study, we aimed to evaluate the effect of the addition of different probiotics to commercial diets for piglets on diet digestibility, total bacterial count (TBC) of faeces, Clostridium count and growth performance. In the digestibility assay, 24 entire male pigs with an average initial body weight of 18.8 ± 0.87 kg were housed individually in metabolism cages and distributed in a completely randomised experimental design; this consisted of three treatments (probiotic-free commercial feed; commercial fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Not surprisingly, this is the phase with the highest incidence of diarrhea and with the highest use of antibiotics [ 56 ]. The association of benzoic acid with probiotics and prebiotics has been suggested to have a synergic effect to favor weaned piglets’ performance [ 37 , 57 , 58 ], which are consistent with the present study. A recent study reported that supplementation of ZnO (1200 ppm) with a probiotic containing Bacillus coagulans, B. licheniformis, B. subtilis and C. butyricum had similar effect than higher doses of ZnO (3000 ppm) on many performance paramethers [ 1 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Not surprisingly, this is the phase with the highest incidence of diarrhea and with the highest use of antibiotics [ 56 ]. The association of benzoic acid with probiotics and prebiotics has been suggested to have a synergic effect to favor weaned piglets’ performance [ 37 , 57 , 58 ], which are consistent with the present study. A recent study reported that supplementation of ZnO (1200 ppm) with a probiotic containing Bacillus coagulans, B. licheniformis, B. subtilis and C. butyricum had similar effect than higher doses of ZnO (3000 ppm) on many performance paramethers [ 1 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Non-dissociated benzoic acid passes through the cellular membrane of bacteria releasing protons that acidify the medium [ 32 ], changing the bacterial metabolism and suppressing essential enzymes, such as decarboxylases and catalases [ 33 , 34 ] Furthermore, benzoic acid improves the structure of the intestinal mucosa, reducing the crypt depth and increasing the villus/crypt ratio culminating in improved digestibility and performance [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model 4 was nearly the equivalent of Model 3 by this criterion for the analysis of gain and was preferred for the analyses of FCR and FBW. Other assessments of growth performance by pigs included covariates in the statistical models that were used to analyse the data (Oliveira et al, 2018;Genova et al, 2019;Oliveira et al, 2019). Additionally, the use covariates in statistical models to control the experimental error could minimize the number of experimental units required for robust experimentation (Jacobs et al, 2013).…”
Section: Resultsmentioning
confidence: 99%